News of Islamic Blasphemy onthe Websites of Kompas and Republika: A Critical Discourse Analysis - ., Nuryadi; Suganda, D; Sunarni, N; Darmayanti, N (KnE Social Sciences, 2018)
This article presents the views of Kompas and Republika regarding the news of religious blasphemy committed by Basuki Tjahaja Purnama (BTP), the governor of Jakarta from 2014 to 2017. Kompas is considered to be close to Christians while Republika is considered to be close to Muslims. The objective of the study is to understand the views of Kompas and Republika in delivering news of Islamic religious blasphemy through the use of language. The research method used in this study is a descriptive qualitative method using Van Dijk’s CDA approach, which consists of text analysis, social cognition analysis, and social context analysis. The data analyzed are samples of religious blasphemy news obtained from the website of Kompas and Republika between September 2016 and April 2017, each media is taken randomly 15% of total news. The results of the analysis show that the website of Kompas has a tendency to say that BTP did not insult religion and the court process was not fair while the website of Republika has a tendency to say that BTP was blasphemous. Both media expressed their views by creating the meaning which refers to the view of each newspaper using macrostructure elements that involve news titles, topic development, and news structure development, and microstructure elements that involve the usage of syntactic, semantic, and rhetorical aspects. Keywords: critical discourse analysis, Jakarta gubernatorial election, macrostructure, microstructure, religious blasphemy, van Dijk’s theory of CDA